2014
DOI: 10.1007/s00449-014-1303-5
|View full text |Cite
|
Sign up to set email alerts
|

High-productivity lipid production using mixed trophic state cultivation of Auxenochlorella (Chlorella) protothecoides

Abstract: A mixed trophic state production process for algal lipids for use as feedstock for renewable biofuel production was developed and deployed at subpilot scale using a green microalga, Auxenochlorella (Chlorella) protothecoides. The process is composed of two separate stages: (1) the photoautotrophic stage, focused on biomass production in open ponds, and (2) the heterotrophic stage focused on lipid production and accumulation in aerobic bioreactors using fixed carbon substrates (e.g., sugar). The process achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…Regarding lipid content, it was found that higher availability of nitrogen in the photoautotrophic cultures resulted in higher lipid content (p < 0.05). These results are not in line with other studies on A. protothecoides, which report lipid contents of more than 50% [35,36]. It appears that the strain used in this study under the specific conditions resulted in the accumulation either of proteins (when grown under nitrogen replete conditions) or carbohydrates (when grown under low nitrogen availability).…”
Section: Biochemical Composition and Pigment Content Of A Protothecoidescontrasting
confidence: 98%
“…Regarding lipid content, it was found that higher availability of nitrogen in the photoautotrophic cultures resulted in higher lipid content (p < 0.05). These results are not in line with other studies on A. protothecoides, which report lipid contents of more than 50% [35,36]. It appears that the strain used in this study under the specific conditions resulted in the accumulation either of proteins (when grown under nitrogen replete conditions) or carbohydrates (when grown under low nitrogen availability).…”
Section: Biochemical Composition and Pigment Content Of A Protothecoidescontrasting
confidence: 98%
“…Oleic acid (C18:1 up to 55.6%), linoleic (C18:2 up to 19.8%), and palmitic acid (C16:0 up to 12.5%) were the major components of all the three oil categories and contributed more than approximately 85% to the total fatty acids. Similar results for lipid biosynthesis were observed by Rismani-Yazdi et al [ 48 ] during the cultivation of A. protothecoides in a heterotrophic semicontinuous system in glucose. In the present study, there were no significant differences in the fatty acids profiles between the two trophic modes applied.…”
Section: Resultssupporting
confidence: 89%
“…Namely, under mixotrophic conditions, the percentages of the major fatty acids produced were: 61.2% for oleic, 18.8% for linoleic, and 11.4% for palmitic acid. Rismani-Yazdi et al [48], in contrast, observed different fatty acid compositions between photoautotrophically and heterotrophi- Fourteen different types of fatty acids, including saturated, monounsaturated, and polyunsaturated, were detected in the heterotrophic mode culture. Oleic acid (C18:1 up to 55.6%), linoleic (C18:2 up to 19.8%), and palmitic acid (C16:0 up to 12.5%) were the major components of all the three oil categories and contributed more than approximately 85% to the total fatty acids.…”
Section: Lipidsmentioning
confidence: 91%
“…In heterotrophic cultivation, organic carbon is instead utilized as a structural and energy source and no light is needed to support growth. Thus, heterotrophic organisms can grow in closed bioreactors, reaching biomass concentrations up to 100 g L −1 12–14 and lipid productivities as high as 10–15 g L −1 d −1 15 (Table S1 ‐ Supplementary data). Such biomass concentrations are about 100 times higher than those obtained in autotrophic cultivation, which reduces dilution and harvesting costs.…”
Section: Introductionmentioning
confidence: 99%